Identifying novel genetic loci associated with polycystic ovary syndrome based on its shared genetic architecture with type 2 diabetes - Li, Xiaoyi; Xiao, Han; Ma, Yujia; Zhou, Zechen; Chen, Dafang (Frontiers in Genetics, 2022)
Genome-wide association studies (GWAS) have identified several common variants associated with polycystic ovary syndrome (PCOS). However, the etiology behind PCOS remains incompletely known. Available evidence suggests a potential genetic correlation between PCOS and type 2 diabetes(T2D). The publicly available data may provide an opportunity to enhance understanding of PCOS etiology. Here we quantified the polygenic overlap between PCOS and T2D using summary statistics of PCOS and T2D and then identified the novel genetic variants associated with the PCOS behind this phenotypic association. A bivariate causal mixture model (MiXeR model) found a moderate genetic overlap between PCOS and T2D (Dice coefficient = 44.1%, and after adjusting for body mass index, 32.1%). Conditional/Conjunctional false discovery rate method identified 11 potential risk variants of PCOS conditional on associations with T2D, 9 of which were novel and 6 of which were jointly associated with two phenotypes. Functional annotation of those genetic variants supports a significant role for genes involved in lipid metabolism, immune response, and insulin signaling pathway. Expression quantitative trait loci functionality analysis successfully repeated that 5 loci were significantly associated with the expression of candidate genes in many tissues, including the whole blood, subcutaneous adipose, adrenal gland, and cerebellum. We found that SCN2A gene is colocalized with PCOS in subcutaneous adipose using GWAS-eQTL colocalization analyses. 11 candidate genes were differentially expressed in multiple tissues of PCOS samples. These findings provide a new understanding of shared genetic architectures between PCOS and T2D and the underlying molecular genetic mechanism of PCOS.